Application of Numbered Head Together Type Cooperative Learning Model to Overcome Learning Saturation of Elementary School Students - Jayangti; Baderiah; Firman; Salam (South Sulawesi Education Development (SSED), 2022)
This study aims to determine the application of the NHT (Numbered Head Together) type of cooperative learning model to overcome student learning saturation. This type of research is PTK with research instruments using observations, questionnaire sheets, and documentation. The results of this study were high precyclical; there were ten students (43.48%), nine students (39.13%), and low only four students (17.39%). On the other hand, cycle I result in a learning saturation of 5 students (21.74%), which is still high, medium 14 students (60.87%), and low remaining four students (17.39%). In comparison, cycle II students who are high in learning saturation 0 students (0.00%), medium eight students (34.78%), and low 15 students (65.22%) can be concluded that learning saturation in students has decreased quite rapidly, and answers the problem in this study, namely the completion of learning saturation in grade IV students of SD Negeri 8 Salobulo Kota Palopo.